Strategi Guru Madrasah Diniyah dalam Menanamkan Pendidikan Karakter Religius dan Karakter Nasionalisme - Munawaroh, Aqilatul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The impact that occurs during distance learning provides learning system knowledge related to teacher learning strategies in instilling religious character education and nationalism characters. This study uses Hamzah B. Uno's theory regarding learning strategies which include: organizing strategies, delivery strategies, and teaching management strategies. This study uses a type of qualitative research. The data analysis used is descriptive qualitative. The results of the research are: 1) The teacher's strategy in instilling religious character education is as follows: a) organizational strategy: yellow book, b) Delivery strategy: expository strategy using methods of inculcating moral and religious knowledge, habituation methods, exemplary methods and giving advice, c ) Learning management strategy: HSPK as a reference in conveying material. (2) The teacher's strategy in instilling nationalism character education is as follows: a) Organizational strategy: the book of the Salaf or the yellow book, b) Delivery strategy: Expository strategy using the method of instilling knowledge and habituation methods, c) Learning management strategy: HSPK.